2020
DOI: 10.1097/md.0000000000023327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms, comorbidities and complications in severe and non-severe patients with COVID-19

Abstract: Background: The pandemic of COVID-19 poses a challenge to global healthcare. The mortality rates of severe cases range from 8.1% to 38%, and it is particularly important to identify risk factors that aggravate the disease. Methods: We performed a systematic review of the literature with meta-analysis, using 7 databases to identify studies reporting on clinical characteristics, comorbidities and complications in severe and non-severe patients with COVID-19. All the obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 22 publications
6
40
1
4
Order By: Relevance
“…After adjustment for other risk factors, we found only a weak association between cardiovascular disease and non-ICU hospitalization for COVID-19, and we found no association with ICU hospitalization. This result contradicts the findings of systematic reviews and meta-analyses [ 25 27 ]. Previous observational studies have shown conflicting results, perhaps in part due to differences in definition [ 5 , 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 88%
“…After adjustment for other risk factors, we found only a weak association between cardiovascular disease and non-ICU hospitalization for COVID-19, and we found no association with ICU hospitalization. This result contradicts the findings of systematic reviews and meta-analyses [ 25 27 ]. Previous observational studies have shown conflicting results, perhaps in part due to differences in definition [ 5 , 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 88%
“…We did not capture symptoms such as fatigue, disturbances in taste and smell, and anxiety, widely reported in post-covid syndrome 24. Although we focused on outcomes after discharge for patients admitted to hospital for covid-19, a sizeable minority of individuals (38%) had not been discharged alive by the end of the study period, as reported globally 3435…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, diabetes, and cardiovascular diseases were soon identified as common comorbidities in COVID-19 patients ( 1 , 2 ). The following studies revealed that hypertension is an important risk factor for adverse outcomes in COVID-19 patients ( 3 , 4 ). Initial studies reported hypertension as an independent predictor of hospitalization, an advanced stage of pneumonia, admission to the intensive care unit (ICU), and mortality in these patients ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%